Escutas de histórias de amor - Baboni, Renata (2021)
The thesis expresses love things, like love histories, children, interruptions, rubbish, writings, death, life, and so many others. It works through the composition, and the connection between the singularities that emerge in the love histories listened to during the project “Escutas de Histórias de Amor.” In each story, I present a different Renata, which unfolds herself and strengthens a process of metamorphosis during the thesis. Here, the desire to tell a story about the interruption of love met the desire to listen to it lovingly by making it possible to develop listening as a kind of interruption in the loving history, which confounds itself with other stories disempowers life. The listening to the interruptions present in each loving story was experienced in their variations, even as an analytic articulation, summoning its love vestiges (or cacarecos amorosos) to the listening and the creative experimentation that affirms life. These love histories make up one and many stories of the life that wants to thrive